Dendritic cell functions: Learning from microbial evasion strategies. Issue 2 (March 2015) - Rescigno, Maria
Highlights: Microorganisms can interfere with recognition, antigen processing and presentation, and killing by macrophages and dendritic cells. Each pathogenic microorganism has developed unique strategies to evade APC recognition. Understanding how microorganisms evade the immune response can shed light on how APCs interact with microorganisms. Abstract: Dendritic cells (DCs) are specialized antigen presenting cells (APC) that are fundamental to initiate both immunity and tolerance. DCs play a 'sentinel' role to protect our body from potential pathogens and induce tolerogenic responses toward harmless antigens. The flexibility of DCs or macrophages to adapt to the environment and to respond accordingly can be hijacked by pathogens for their own interest to transform a potentially immunogenic APC into a tolerogenic cell with clear consequences in pathogen clearance. While these immune evasion mechanisms can be detrimental for the host, they can highlight important molecular pathways in DCs necessary for their function. In this review we will mention several mechanisms employed by pathogens to evade DC patrolling function.